2018
DOI: 10.20944/preprints201810.0288.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential Effects of Red Yeast Rice, Berberis Aristata and Morus Alba Extracts, Active Components of LopiGLIK®, on PCSK9 in HepG2 Cells

Abstract: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is the key regulator of low-density lipoprotein cholesterol (LDL-C) plasma levels. We previously observed that treatment of dyslipidemic subjects with nutraceutical combination containing red yeast rice (monacolin K 3.3 mg), Berberis aristata cortex extract (Berberine 531.25 mg) and Morus alba leaves extract (1-deoxynojirimycin 4 mg) (LopiGLIK®) did not alter the plasma PCSK9 levels. Thus, the aim of the present study was to investigate the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Firstly, to evaluate the effects on HepG2 cells leading to finding the non-toxic concentration, a dose–response study was performed, testing the extracts in a range reported in the literature. Indeed, the cells were treated with increasing concentrations of sage extract (from 0.029 to 0.3 µM) [ 12 ], Red Yeast Rice (RYR, from 1 to 50 µM) [ 10 ], Vitamin D3 (from 1 to 100 nM) [ 38 ], Resveratrol (from 1 to 40 µM) [ 39 ], Quercetin (from 5 to 10 µM) [ 40 ], Astaxanthin (from 1.7 to 17 nM) [ 41 ], CoQ10 (from 1 to 100 µM) [ 42 ], Vitamin K2 (from 0.01 to 1 µM) [ 43 ], Sodium Selenite (from 1 to 10 µM) [ 44 ], Folic Acid (from 25 to 75 µg/mL) [ 45 ]. The best concentration of each extract was maintained for all successive experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, to evaluate the effects on HepG2 cells leading to finding the non-toxic concentration, a dose–response study was performed, testing the extracts in a range reported in the literature. Indeed, the cells were treated with increasing concentrations of sage extract (from 0.029 to 0.3 µM) [ 12 ], Red Yeast Rice (RYR, from 1 to 50 µM) [ 10 ], Vitamin D3 (from 1 to 100 nM) [ 38 ], Resveratrol (from 1 to 40 µM) [ 39 ], Quercetin (from 5 to 10 µM) [ 40 ], Astaxanthin (from 1.7 to 17 nM) [ 41 ], CoQ10 (from 1 to 100 µM) [ 42 ], Vitamin K2 (from 0.01 to 1 µM) [ 43 ], Sodium Selenite (from 1 to 10 µM) [ 44 ], Folic Acid (from 25 to 75 µg/mL) [ 45 ]. The best concentration of each extract was maintained for all successive experiments.…”
Section: Methodsmentioning
confidence: 99%
“…For example, it is suggested that polyphenolic compounds can be used to activate AMPK to reduce oxidative damage and inflammation, which play a critical role in the development of chronic disease [ 9 ]. In nature, several nutraceutical combinations have shown significant lipid-lowering effects and a potential positive impact on cardiovascular risk by modulating the proprotein convertase subtilisin/kexin type 9 (PCSK9) factor which plays a particular role in regulating LDL-C levels by degrading the LDL receptor (LDLr) [ 10 ]. Based on all these results it is important to resolve the claim about some nutraceuticals with RYR by studying the combined effects of several active ingredients, such as Sage extract, Resveratrol, Folic Acid, vitamin D3, Quercetin, Astaxanthin, and CoQ10.…”
Section: Introductionmentioning
confidence: 99%